Enhancing University Students' Digital Behavior: Exploring Individual Learning and Team Leadership Intervening - Trihantoyo, Syunu; Windasari, Windasari; Sa'ari, Noor Akhmarisha Binti; Rifqi, Ainur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Individual learning in students is considered only partially optimal in supporting current digital competencies. To fulfill digital behavioral competencies, team leadership interventions are required through various learning activities undertaken by students. This study aims to analyze the influence of individual learning on students' development of digital behavior mediated by team leadership. Quantitative research methods with AMOS Structure Equation Model (SEM) analysis were carried out with the following stages: validity and reliability testing; SEM model suitability testing to determine the Goodness of Fit model by looking at the Chi-Square, Probability, RMSEA, GFI, AGFI, CMIN/DF, TLI, CFI, and NFI values; research hypothesis testing. The research sample consisted of 301 respondents who were taken randomly from students of Surabaya State University who were implementing the emancipated learning program. This study showed that individual learning affected students' digital behavior. Meanwhile, the mediating role of team leadership on the influence of individual learning on digital behavior consists of dimensions: opportunity to develop (not mediating), transparency (mediating), and creativity (not mediating). The implication of this research shows that the dimensions of transparency that shape students' digital behavior are openness in the learning process, transparent access to information, honest assessment, and open team communication.